PENERAPAN DOKTRIN FOREIGN EQUIVALENTS PADA PENDAFTARAN MEREK DAGANG DI INDONESIA - Maya Ruhtiani (J-LEE - Journal of Law, English, and Economics, 2023)
Trademark registration is very important for businesses so that the trademark that has been built is not imitated by others, but in reality, the registration of trademarks in the Directorate General of Intellectual Property does not rule out the possibility of disputes caused by the registration of trademarks that have similarities with other trademarks or even have similarities in meaning with previously registered trademarks. This research discusses the application of the doctrine of foreign equivalents associated with trademark registration in Indonesia which aims to be a solution when there is a dispute in the trademark registration process. The research method used is normative legal research using legal materials relevant to trademark registration in Indonesia. The results showed that the concept of the doctrine of foreign equivalents is done by translating a trademark or service mark into English before the mark is registered. It is intended that the registered trademark can be identified whether the trademark is a generic trademark or included in the words of public property or there is a resemblance to a previously registered trademark. In addition, the doctrine of foreign equivalents has not been applied in Indonesia, it can be proven by the existence of two different court decisions related to trademark registration associated with the concept of foreign doctrine.